The Historical Development of the Words “Dissociation” and “Ionization” in Chemistry - Carriello, Giovanni Miraveti; Manassés Pegoraro, Guilherme; Batista dos Santos Junior, João (Revista Debates em Ensino de Química, 2023)
The words "dissociation" and "ionization" are sources of misconceptions in chemistry teaching, mainly in the subjects of acids and bases, chemical equilibrium and solutions. In the present article, the historical development of the two words was analyzed. Ever since the ending of the 19th century, with the studies of Berthelot, Arrhenius and Ostwald, until the middle of the 20th century, the general use of these words was made independently, with no clear differentiation between them, in some cases being used interchangeably. This idea was changed with the introduction of new atomic models by Thomson, Rutherford and Bohr, other conceptions of acids and bases, as proposed by Lewis, and research with gases and solutions. With the first recommendations of the International Union of Pure and Applied Chemistry (IUPAC) in the sixties and Herron's questionnaire in the seventies, the first formal differentiations between "dissociation" and "ionization" started to emerge. Driscoll proposed using the words based on whether ions already existed in the structure of the chemical entity and could be separated. In the nineties, IUPAC defined the two words formally, and their definitions were not mutually exclusive. A few years later, Schultz and Adams proposed a differentiation based on whether the chemical species interacted with water (e.g., solvation) or reacted with water (e.g., producing hydronium). Currently, IUPAC recommendations, academic publications and textbooks use the words in an irregular manner, perpetuating the difficulties in chemistry when "dissociation" and "ionization" phenomena are taught.